EMPLOYMENT ADJUSTMENT AND LEADERSHIP CAPABILITY DURING A PANDEMIC COVID-19 AND ITS IMPLICATIONS FOR HUMAN RESOURCE MANAGEMENT IN INDUSTRY IN JAKARTA - Sutarman, Asep; Nugroho, Arif Widodo; Anjani, Frida Kusuma; Arthamevia, Azzura Kania (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
The performance of industrial human resources is an indicator of whether the production process of industrial workers in an industrial project is good or bad. In an effort to improve performance, work experience is needed. Work experience reflects proficiency in the knowledge and skills possessed by a workforce in a job that can be measured from the years of service and the type of work carried out by the workforce. This study aims to identify, analyze and demonstrate empirically the effect of job adjustment, leadership ability on human resource management in industry in Jakarta. This research was conducted with quantitative research methods. The population of this study are employees or employees of several industrial companies in Jakarta. Data collection techniques by observation, literature study, interviews and questionnaires. The final conclusion of this paper is that there is an effect of employment adjustment on human resource management. So, with large-scale social restrictions, with the stipulation of work from home, massive layoffs do not affect HR management policies. Furthermore, we know that there is an influence of leadership on human resource management. Where a leader has primary responsibility for the business, acting as a change maker for the organization Keywords: Employment Adjustment; Leadership Ability; Human Resource Management; Covid-19